THE SYMBOLIC MEANINGS OF WHITE COLOR IN ENGLISH AND CHINESE - Liu Xuemei, (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
Under the influence of different languages and cultural factors, people have not entirely the same emotions towards certain specific vocabulary, such as color terms, and maybe different in understanding their implicit symbolic meanings as well. Even in the same culture background, for the sake of individual experience, historical influence, context, characteristics as well as ethnic aesthetic psychology and cognitive emotions, interpretations and emotional responses might diverse among different ethnic groups. This paper tries to explore similarities and the diversities of the symbolic meanings of commonly used color words in English and Chinese, so as to enhance the awareness of cross-culture language teaching and communication, help students better understand the languages and cultures.